Development and Validation of an Ethnochemistry Integrated Digital Pop Up Book for Acid–Base Instruction - Mawarnis, Elvy Rahmi; Sari, Dwivelia Aftika; Lestari, Amanda (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study develops and evaluates a novel ethnochemistry based digital pop-up book for teaching acid–base concepts at the senior high school level. The novelty of this research lies in integrating local Minangkabau cultural practices with interactive digital pop up media to address the abstract nature of acid–base learning. The study employed a Research and Development approach using the 4D model (define, design, develop, and limited dissemination). Data were obtained through expert validation and limited field testing involving a chemistry teacher and Grade XI students. The media combines animations, videos, interactive navigation, contextual ethnochemistry content, and formative assessments within a single digital learning platform. Expert validation results across material, language, media design, and ethnochemistry aspects indicated a highly valid category. Practicality testing demonstrated very practical outcomes in terms of usability, attractiveness, usefulness, and time efficiency. These findings confirm that the developed media offers an innovative, contextual, and effective solution for enhancing conceptual understanding and student engagement in chemistry learning.